Paraquat Poisoning and AKI –A Rare Pediatric Case Report in a Tertiary Care Hospital - Biswas, Susmita; Barua, Paramita; -Quader, Mohammed Maruf-ul; Chowdhury, Dhiman; Biswas, Suman; Das, Abir (Journal of Pediatric Nephrology, 2021)
Paraquat is a widely used synthetic herbicide in agriculture. Ingestion of toxic doses of paraquat can be fatal with life threatening effects on the kidneys, lungs, gastrointestinal tract (GIT), liver, heart, and other organs. There is no specific antidote or effective life saving treatment for paraquat poisoning and its prognosis is very poor worldwide. Here we report a case that presented with acute renal failure, shock, GIT bleeding with oral mucosal ulceration, and pulmonary involvement due to accidental paraquat poi soning and delayed hospitalization after poison ingestion. In spite of partial improvement, the patient expired after two weeks of admission. Therefore, any case of paraquat poisoning must be hospitalized and, if needed, referred to equipped centers as early as possible after poison ingestion